Active Learning Strategies In Language Acquisition: A Study With Saudi EFL Preparatory School Students - Alwehebi, Kholoud Abdullah Ibrahim (Journal of Posthumanism, 2025)
This study aims to assess the impact of active learning on English language acquisition among Saudi EFL preparatory school students. It examines the correlation between active learning strategies and students' language acquisition. A mixed-methods approach incorporating both quantitative and qualitative research was employed, involving 122 students and seven teachers from Saudi schools. Data collection instruments included a closed-ended questionnaire measuring students’ attitudes towards active learning and its impact on language acquisition, as well as open-ended interviews with teachers. The findings indicate that students exhibit highly positive attitudes towards active learning strategies implemented by their teachers (Mean = 3.85). Inferential analysis using Pearson’s correlation coefficient reveals a moderately high correlation between active learning and language acquisition (r = .686, p < .01).